A influência de um Active Learning Space na capacidade de resolução de problemas complexos - Garcia, Cristiano (2019)
Problem solving is a fundamental competence to be developed and appropriated by individuals and should be seriously considered in the education of children and youth. National studies, such as Affero Lab (2016), and international reports of high social impact, such as The World Economic Forum (2016), point to new cognitive domain skills needed by professionals of this century, being Complex Problem Solving the most outstanding. In order to understand how learning spaces can influence the development of this competency so relevant to students in the 21st century, we sought to explore the potential of Active Learning Spaces as spaces that mobilize cognitive skills linked to solving complex problems. From a bibliographic research and qualitative methodological procedures, the research was exploratory and approached in action research. The data production instruments were observations, questionnaire and interview. The activities were based on Design Thinking with a group of students from the Integrated High School Center of the University of Passo Fundo. The results of this research indicate that disruptive learning environments are important elements for education and when combined with the use of digital technologies, methodological approaches and activities through experimentation, they stimulate stimuli and contribute to a more meaningful and reflective learning for students.